Adolescents with Type I Diabetes Mellitus and their Knowledge about the Disease - Marisleidy Denis Rodríguez; Antonio Masot Rangel; Nicolás Ramón Cruz Pérez; Juan Carlos Yanes Macías; Mayumi Hernández Díaz (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Background: diabetes mellitus is an endocrine-metabolic disease characterized by high levels of glucose in blood that occurs due to a deficient secretion or action of insulin. It is a growing health problem. Objective: to identify what knowledge adolescents with type I diabetes mellitus have at the Paquito González Cueto Cienfuegos University Pediatric Hospital. Method: a descriptive cross-sectional study was carried out with 42 adolescents diagnosed with type I diabetes mellitus who are followed up in the endocrinology clinic of the Cienfuegos University Pediatric Hospital. The variables analyzed were: age, level of education, time of diagnosis of the disease and knowledge related to diabetes mellitus. A previously validated questionnaire was designed to obtain information. Results: the 30 (71.4 %) patient they answered the concept of the disease correctly. The group of 14 was 16 elderly years the most represented of 20 patients. They were marked as to the symptoms correct over the 60 %. The level of prevailing scholarship was secondary basic and they were the 83.3 % evaluated of good. The teens with 1 to 2 years of diagnosis obtained a satisfactory evaluation 7 (58.3 %). Conclusions: the largest number of patients was between 14 and 16 years old. There were difficulties in identifying decompensating symptoms, as well as in dietary treatment. The largest number of patients studied obtained a satisfactory evaluation.